2014
DOI: 10.1071/eg12026
|View full text |Cite
|
Sign up to set email alerts
|

Site characterisation in north-western Turkey based on SPAC and HVSR analysis of microtremor noise

Abstract: The geology of the north-western Anatolia (Turkey) ranges from hard Mesozoic bedrock in mountainous areas to large sediment-filled, pull-apart basins formed by the North Anatolian Fault zone system. Düzce and Bolu city centres are located in major alluvial basins in the region, and both suffered from severe building damage during the 12 November 1999 Düzce earthquake (Mw = 7.2). In this study, a team consisting of geophysicists and civil engineers collected and interpreted passive array-based microtremor data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…While H/V is traditionally considered to be only sensitive to the shallow-surface (i.e. the first 200 m) (Nakamura 1989) or to intermediate depth (Asten et al 2014) , recent studies demonstrated the feasibility of modelling it to image deep interfaces down to several kilometres (Spica et al 2015(Spica et al , 2018a. One well-known problem is that H/V measurement at the surface is generally insufficient to characterize shallow properties because a proportional change in layer velocities and thicknesses leads to similar H/V (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While H/V is traditionally considered to be only sensitive to the shallow-surface (i.e. the first 200 m) (Nakamura 1989) or to intermediate depth (Asten et al 2014) , recent studies demonstrated the feasibility of modelling it to image deep interfaces down to several kilometres (Spica et al 2015(Spica et al , 2018a. One well-known problem is that H/V measurement at the surface is generally insufficient to characterize shallow properties because a proportional change in layer velocities and thicknesses leads to similar H/V (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2). At many sites in the downtown area of Gangneung (12%), S-wave velocity are lower than 200 m/s and consequently substantial risk of soil-liquefaction is apprehended in the case of strong ground motions (Asten et al, 2014 Preliminary results of the seismic microzonation and site characterization of three major cities of Gangwon province, Korea using Rayleigh-wave Dispersion curves…”
Section: Vs30 and Seismic Site Zonationmentioning
confidence: 99%
“…The surface rupture due to the 12 November 1999 Düzce earthquake was measured as a 45-km surface along with horizontal and vertical displacements of 3 and 5 m, respectively (Sahin and Tari 2000). Düzce city is built on an alluvial basin composed of soft soil media (Asten et al 2014). The sediment thickness is estimated as * 260 m for Düzce basin using geological data (Sengor et al 2005).…”
Section: Study Areamentioning
confidence: 99%
“…The 1D velocity models have been presented in Bulut et al (2007) for the Izmit region, by Bouin et al (2004), Umutlu et al (2004) and Konca et al (2010) for the Düzce region, and by Asten et al (2014) for both the Bolu and Düzce regions. In this study, the velocity models by Asten et al (2014) are used for low-frequency simulations at the Bolu and Düzce stations. For the GYN station, the only velocity model available is the 1D model down to only 30 m from the Turkish strong-ground-motion database.…”
Section: Study Areamentioning
confidence: 99%